Changes in calcaneal pitch and heel fat pad thickness in static weight bearing radiographs while wearing shoes with arch support and heel cup orthotics - Hiroshi Ohuchi; Joverienne S. Chavez; Carlo Antonio D. Alvarez (Elsevier, 2019)
Background: Foot orthoses have been shown to reduce the collapse of the longitudinal arch and to constrain soft tissue displacement under the heel. However, there has not been a study that has shown the effectiveness of both the arch and heel features in the same orthosis. This study quantitatively analyzed if the calcaneal pitch and the heel pad thickness will be affected by the use of an arch support and heel cup insole in a static weightbearing stance while wearing sports shoes. Methods: Twenty-four (24) feet from 12 elite-level female soccer players with a mean age of 25 ± 3.99 years (20-33 years old) were studied. Lateral weightbearing radiographs with and without orthotics were obtained in order to measure the calcaneal pitch angle and heel fat pad thickness for each foot. A subjective outcome measure was used and the scores were classified as bad (0-2), fair (3-5), good (6-8), or excellent (9-10). Results: The calcaneal pitch angle increased in all but three cases by an average of 1.05° (range, −1.14 to 3.19) after wearing orthotics (p < 0.01). The heel fat pad thickness increased in all cases with an average of 1.25 mm (range, 1.05 to 1.47; p < 0.01)). 9 of 12 subjects (75%) reported excellent (n = 2) or good (n = 7) overall subjective scores with insole wear. Conclusion: Under static weightbearing conditions, the arch support and heel cup features of a foot orthosis help improve the height of the calcaneal pitch and the thickness of the heel fat pad, respectively. Keywords: Foot orthoses, Arch support, Heel cup, Calcaneal pitch, Heel fat pad thickness